The Effect of Professionalism and Accountability for Audit Quality - Reiy Sakila (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the effect to professionalism and accountability on the audit quality at the company PT.Pindad (Persero). This research is done at PT.Pindad company in Bandung city. The number of samples taken was 35 people. Data collection methods used in this study are conducting surveys and distributing questionnaires. Data analysis techniques used are descriptive and verification methods by changing ordinal data from questionnaires to interval data, using the Method of Succesive Interval (MSI). Where as to answer the research hypothesis using classical assumption analysis and multiple regression analysis, usisng SPSS version 23. Based on the results it can be seen that professionalism, accountability positively affect the audit quality at PT.Pindad (Persero) in Bandung.